Epidemiological and Clinicopathological Analysis of Odontogenic Tumors: A 20-Year Study - Molook Torabi; Mahta Khosrozamiri; Maryam Alsadat Hashemipour (Association of Support to Oral Health Research (APESB), 2024)
Objective: To perform the epidemiological and clinicopathological analyses of odontogenic tumors in Kerman for 20 years. Material and Methods: The present study investigated collected records from pathology departments of the Faculty of Dentistry, Bahonar, and Shafa teaching-medical hospitals for 20 years. Data on odontogenic tumors was recorded based on age, sex, and tumor location in the information forms. The statistical t-test and the Kappa coefficient computer codes were utilized for data analysis. Results: 38 samples of odontogenic tumors were considered in the present study. The mean age of participants was 31.7± 10.3 years. The frequency of tumors was higher in women (63.2%) and in the lower jaw) 78.9%). Among various tumors, ameloblastoma (63.1%) and odontoma (18.4%) were the most common tumors, respectively. The correlation between clinical and histopathologic diagnoses was 71.8% using the kappa coefficient. Conclusion: Ameloblastoma is the most common odontogenic tumor. The incidence of lesions was higher in the mandible, and odontogenic tumors were higher in women. Since the diagnosis of odontogenic tumors is based on radiographic and histologic appearances, clinical physicians and pathologists should collaborate for the definitive diagnosis of the disease.